Persepsi Pemain dan Pelatih terhadap Peran Futsal dalam Mengembangkan Kemampuan Pengambilan Keputusan Pemain Sepakbola Wanita - Ramadhan, Muhamad Hanif; Fitri, Mustika; Kurniawan, Tian; Nilan, Fariha; Nevitaningrum (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this study is to find out whether futsal can help female football players become better at making decisions in the game.  This study used a survey to find out the opinions of players and coaches about the function of futsal.  Questionnaires were the research tools used to measure the perceptions of players and coaches.  The purposive sampling method was used to select the sample.  The survey results show that most futsal players and coaches agree that playing futsal helps them make decisions in football game situations. They also said that most futsal players and coaches believe that playing futsal helps them make decisions.  This research is expected to help female football players make better decisions. Therefore, it is recommended to female football players to increase the portion of training by playing futsal, while coaches can incorporate futsal into the training programme as an alternative to small sided games (SSG) to develop players' playing and decision-making skills.